Types of Housing Defects that Appear in Malaysia Using Defect Index (DI) Method - Bueraheng, Decha (Universiti Teknologi Petronas, 2011)
Malaysia is among the developing countries and many projects are be implemented. Currently, some of these projects include the construction buildings. The construction industry contributes to generating the economy and such as the provision of services to construction companies but some of these listed companies lack of professionalism by getting involved in projects that are not in the standard, especially Housing Development. There are many defects in the Purchased homes of the house Buyers, particularly in terms of material and processing. This study is conducted to identify the defect level based on common types of housing defect that appear in Malaysia by using Defect Index (DI) Method based on 15 building elements proposed by Pedro (2008) to be a framework of tropical housing and the result from this study can assist the contractors and developers to concern more on particular building elements that have medium high level of defects. The methodology adopted is through literature review and a questionnaire survey are used as data collection mechanism and it is prepared, distributed and collected within a short period of time to the respondents involve in Malaysia Property Exposition 20 II (MAP EX 2011) in Perak and Klang Valley. The result shows that the terrace houses that were built in Kuala Lumpur for less than 5 years, there are severe defects on Electricity Installation and Water service but there is a medium defect on Drainage.Otherwise, the apartments and terrace houses that were built in Perak for more than 5 years but less than 15 years, there is a medium defect on Electricity Installation but there are severe defect on Water service and Drainage. In order to minimize the defect level, the contractors and developers should do the improvement on the elements that have severe defects which are water service and drainage system and also for the elements that have medium defect which is electricity installation. This improvement is for the better quality of the houses and will decrease the hous~ users' complaint.